Powder coating for coastal photovoltaic field steel structure and preparation method and application thereof
By using organosiloxane modified polyester polymer powder coating to form a cross-linking anti-corrosion coating, the problem of corrosion-prone steel structure brackets in coastal photovoltaic equipment is solved, and the effect of significantly improving corrosion resistance and extending the equipment life is achieved.
Patent Information
- Application Number
- CN202411700759.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-26
- Publication Date
- 2025-02-25
AI Technical Summary
The steel structure brackets of coastal photovoltaic equipment are susceptible to corrosion by the atmosphere and water, resulting in a shortening of the equipment life. Existing corrosion-resistant technologies such as galvanized materials have problems with insufficient corrosion resistance.
A powder coating including an organosiloxane modified polyester polymer is used, which forms an anti-corrosion coating through cross-linking reaction and prevents light-induced chemical reactions under the action of an ultraviolet absorber, thereby improving anti-corrosion performance.
This powder coating can significantly improve the corrosion resistance and weather resistance of steel structure brackets, extend the service life of photovoltaic equipment, and resist salt corrosion in seawater.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] This invention belongs to the field of coating technology, specifically relating to a powder coating for steel structures in coastal photovoltaic fields, its preparation method, and its application. Background Technology
[0002] Compared to onshore photovoltaics, marine photovoltaics have natural environmental advantages: open water surfaces without obstructions, longer and more abundant sunshine, which can significantly increase power generation. However, under natural exposure along the coast, the steel structure supports of photovoltaic equipment react with iron ions and hydroxide ions to form unstable ferric hydroxide, which eventually oxidizes into rust. Corrosion of coastal photovoltaic steel structure supports is mainly due to atmospheric corrosion and water corrosion, caused by oxygen, SO2, and Cl- in the air. - Corrosive media can accelerate the oxidation-reduction reaction of steel structures, causing severe corrosion to photovoltaic supports. Therefore, researching corrosion protection technologies for coastal photovoltaic steel structure supports has practical economic significance.
[0003] Traditional corrosion protection technologies primarily employ galvanized steel structures. Their corrosion resistance relies on the formation of a saturated zinc oxide film with numerous pores during oxidation, reducing further corrosion. However, as corrosive agents (oxygen, moisture, salt, etc.) continuously erode the zinc oxide film, the surface zinc layer thickness diminishes, significantly impacting product lifespan. To address this issue, inventing an ultra-weather-resistant powder coating for marine photovoltaic panel supports is essential to improve the corrosion resistance of steel structure supports and enhance the long-term safe operation of photovoltaic equipment. Summary of the Invention
[0004] In view of this, the present invention provides a powder coating for steel structures in coastal photovoltaic fields, its preparation method and application. The powder coating for steel structures in coastal photovoltaic fields provided by the present invention has good corrosion resistance and weather resistance, and its use in the corrosion protection of coastal steel structure supports can improve the long-term safe operation of marine photovoltaic equipment.
[0005] To address the aforementioned technical problems, this invention provides a powder coating for steel structures in coastal photovoltaic power plants, comprising the following components in parts by weight:
[0006]
[0007]
[0008] The end groups of the organosiloxane-modified polyester polymer include hydroxyl or carboxyl groups.
[0009] Preferably, the method for preparing the organosiloxane-modified polyester polymer includes the following steps:
[0010] Polyester resin, organosiloxane, and catalyst are mixed and subjected to a condensation reaction to obtain the organosiloxane-modified polyester polymer.
[0011] Preferably, the mass ratio of the polyester resin to the organosiloxane is 30-60:40-70;
[0012] The mass ratio of the polyester resin to the catalyst is 30-60:0.5-5.
[0013] Preferably, the condensation reaction is carried out at a temperature of 150–200°C for 4–6 hours.
[0014] Preferably, the powder coating used for the steel structure of the coastal photovoltaic field has a particle size of 120 mesh.
[0015] Preferably, the cyanate compound is triglycidyl isocyanurate and / or a blocked isocyanate.
[0016] The low-temperature accelerator is one or more of monobutyltin oxide, butylstannic acid, and Amanda TH01;
[0017] The degassing agent is benzoin;
[0018] The pigments and fillers include one or more of kaolin, precipitated barium sulfate, mica powder, talc powder, titanium dioxide, and carbon black;
[0019] The flow agent is fumed silica.
[0020] This invention also provides a method for preparing the powder coating for steel structures in coastal photovoltaic fields as described in the above technical solution, comprising the following steps:
[0021] The powder coating for use on steel structures in coastal photovoltaic fields is obtained by mixing organosiloxane-modified polyester polymer, cyanate compound, low-temperature accelerator, polyacrylic resin, anti-scratch agent, brightener, pigments and fillers, degassing agent, UV absorber and flow agent, followed by melt extrusion and crushing.
[0022] Preferably, the temperature of the melt extrusion is 115–150°C.
[0023] The present invention also provides the application of the powder coating described above for steel structures in coastal photovoltaic fields as an anti-corrosion coating for coastal steel structure supports.
[0024] Preferably, the method of using the powder coating for steel structures in coastal photovoltaic fields as an anti-corrosion coating for coastal steel structure supports includes the following steps:
[0025] The powder coating used for steel structures in coastal photovoltaic fields is applied to the surface of coastal steel structure supports and then thermo-cured to obtain an anti-corrosion coating.
[0026] The thermosetting temperature is 170–190°C, and the time is 15–25 minutes.
[0027] This invention provides a powder coating for steel structures in coastal photovoltaic power plants, comprising the following components in parts by weight: 100 parts of organosiloxane-modified polyester polymer, 5-15 parts of cyanate ester compound, 0.2-0.5 parts of low-temperature accelerator, 1-4 parts of polyacrylic acid resin, 1-4 parts of anti-scratch agent, 1-2 parts of brightener, 30-51 parts of pigments and fillers, 0.2-1.0 parts of degassing agent, 0.2-1.0 parts of UV absorber, and 0.1-0.5 parts of flow agent; the end groups of the organosiloxane-modified polyester polymer include hydroxyl or carboxyl groups. This invention introduces organosiloxanes into the polyester, thereby introducing a large number of Si-O-Si bonds, which can prevent the breaking and degradation of the main bonds, increase the bond energy, and give the coating excellent thermal stability. In this invention, the terminal carboxyl or hydroxyl groups in the organosiloxane-modified polyester polymer undergo a cross-linking reaction with the cyanate ester compound under heating conditions to form an anti-corrosion coating. Simultaneously, under the action of a UV absorber, they synergistically prevent light-induced chemical reactions such as the growth and breakage of the organosiloxane-modified polyester polymer backbone, thus improving the effectiveness of the anti-corrosion coating. In this invention, the protective layer formed by the cross-linking reaction between the organosiloxane-modified polyester polymer and the cyanate ester compound during curing effectively shields chloride ions and resists corrosion from salt in seawater. Detailed Implementation
[0028] This invention provides a powder coating for steel structures in coastal photovoltaic power plants, comprising the following components in parts by weight:
[0029]
[0030]
[0031] By weight, the powder coating for steel structures in coastal photovoltaic power plants provided by this invention comprises 100 parts of an organosiloxane-modified polyester polymer; the end groups of the organosiloxane-modified polyester polymer include hydroxyl or carboxyl groups, specifically carboxyl groups. As one embodiment of this invention, the preparation method of the organosiloxane-modified polyester polymer may include the following steps:
[0032] Polyester resin, organosiloxane, and catalyst are mixed and subjected to a condensation reaction to obtain the organosiloxane-modified polyester polymer.
[0033] In one embodiment of the present invention, the polyester resin may be CRYLCOAT 4540-0; the catalyst may be butyltin triisooctanoate.
[0034] In one embodiment of the present invention, the mass ratio of the polyester resin to the organosiloxane can be 30-60:40-70, or 40-45:50-60; the mass ratio of the polyester resin to the catalyst can be 30-60:0.5-5, or 40-50:1-3.
[0035] This invention does not have special requirements for the mixing, as long as it can be mixed evenly. In one embodiment of this invention, the temperature of the condensation reaction can be 150–200°C, or 160–180°C, specifically 160°C, 165°C, 170°C, 175°C, or 180°C; the time of the condensation reaction can be 4–6 hours, or 4.5–5.5 hours. In another embodiment of this invention, the condensation reaction can be carried out in a protective atmosphere, preferably nitrogen.
[0036] In one embodiment of the present invention, the organosiloxane-modified polyester polymer, due to the introduction of organosiloxane, increases the Si-O bond molecular backbone and the d-π bond bond energy, thereby improving the polymer's thermal stability. Simultaneously, the Si-O-Si bonds prevent the backbone from breaking and degrading, forming a protective structural layer. The organosiloxane-modified polyester polymer modified by the present invention exhibits good heat resistance, cold resistance, insulation, and weather resistance, thus improving the protective performance of the coating.
[0037] Based on the mass fraction of the organosiloxane-modified polyester polymer, the powder coating for steel structures in coastal photovoltaic power plants provided by this invention comprises 5 to 15 parts of a cyanate ester compound, which can be 7.3 to 14 parts. As one embodiment of this invention, the cyanate ester compound can be triglycidyl isocyanate and / or a blocked isocyanate, specifically a mixture of triglycidyl isocyanate and a blocked isocyanate, or triglycidyl isocyanate alone. As a specific embodiment of this invention, when the cyanate ester compound is triglycidyl isocyanate and a blocked isocyanate, the mass ratio of the triglycidyl isocyanate to the blocked isocyanate can be 1:2.5 or 1:4.
[0038] Based on the mass fraction of the organosiloxane-modified polyester polymer, the powder coating for steel structures in coastal photovoltaic fields provided by this invention includes 0.2 to 0.5 parts of a low-temperature accelerator, which can be 0.3 to 0.4 parts. As one embodiment of this invention, the low-temperature accelerator can be one or more of monobutyltin oxide, butylstannic acid, and Amanda TH01, specifically monobutyltin oxide, butylstannic acid, or Amanda TH01. As one embodiment of this invention, the monobutyltin oxide catalyst can be FASCAT 4101, and the butylstannic acid catalyst can be 9100 catalyst.
[0039] Based on the mass fraction of the organosiloxane-modified polyester polymer, the powder coating for steel structures in coastal photovoltaic power plants provided by this invention comprises 1-4 parts of polyacrylic acid resin, which can be 2-3.8 parts, or 2.6-2.8 parts. In one embodiment of this invention, the polyacrylic acid resin is preferably HL988 purchased from Huangshan Huahui Technology Co., Ltd. In another embodiment of this invention, the polyacrylic acid resin acts as a leveling agent. In this invention, the polyacrylic acid resin can reduce the interfacial tension between the powder coating and the substrate, increase the wettability of the coating on the substrate, expel gases adsorbed by the binder, and prevent pinholes from forming during the cross-linking and curing process of the coating.
[0040] Based on the mass fraction of the organosiloxane-modified polyester polymer, the powder coating for steel structures in coastal photovoltaic power plants provided by this invention includes 1 to 4 parts of anti-scratch agent, which can be 2.2 to 3.2 parts, or 2.6 to 3 parts. As one embodiment of this invention, the anti-scratch agent can be one or more of NEW-0402, HD-901A, and CJFN-508.
[0041] Based on the mass fraction of the organosiloxane-modified polyester polymer, the powder coating for steel structures in coastal photovoltaic fields provided by this invention includes 1 to 2 parts of brightener, which can be 1.3 to 1.6 parts. As one embodiment of this invention, the brightener can be 701B brightener.
[0042] Based on the mass fraction of organosiloxane-modified polyester polymer, the powder coating for steel structures in coastal photovoltaic fields provided by this invention comprises 30-51 parts of pigments and fillers, which can be 40-44 parts. As one embodiment of this invention, the pigments and fillers may include one or more of kaolin, precipitated barium sulfate, mica powder, talc powder, titanium dioxide, and carbon black; as a specific embodiment of this invention, the pigments and fillers may be a mixture of precipitated barium sulfate, titanium dioxide, and carbon black, a mixture of precipitated barium sulfate, mica powder, titanium dioxide, and carbon black, or a mixture of precipitated barium sulfate, mica powder, talc powder, titanium dioxide, and carbon black; when the pigments and fillers are a mixture of precipitated barium sulfate, titanium dioxide, and carbon black, the precipitated barium sulfate, titanium dioxide, and carbon black... The mass ratio can be 2:1:0.1; when the pigment and filler are a mixture of precipitated barium sulfate, mica powder, titanium dioxide and carbon black, the mass ratio of the precipitated barium sulfate, mica powder, titanium dioxide and carbon black can be 2:1:1:0.1 or 2:1:1:0.1; when the pigment and filler are a mixture of precipitated barium sulfate, mica powder, talc powder, titanium dioxide and carbon black, the mass ratio of the precipitated barium sulfate, mica powder, talc powder, titanium dioxide and carbon black can be 2:1:1:1:0.1 or 1.5:0.8:1.5:0.6:0.1.
[0043] Based on the mass fraction of the organosiloxane-modified polyester polymer, the powder coating for steel structures in coastal photovoltaic power plants provided by this invention includes 0.2 to 1.0 parts of degassing agent, which can be 0.4 to 0.9 parts, or 0.6 to 0.8 parts. In one embodiment of this invention, the degassing agent can be benzoin.
[0044] Based on the mass fraction of the organosiloxane-modified polyester polymer, the powder coating for steel structures in coastal photovoltaic fields provided by this invention includes 0.2 to 1.0 parts of UV absorber, which can be 0.6 to 0.8 parts. As a specific embodiment of this invention, the UV absorber can be one or more of UV-3030, UV-3035, and UV-284.
[0045] Based on the mass fraction of the organosiloxane-modified polyester polymer, the powder coating for steel structures in coastal photovoltaic fields provided by this invention includes 0.1 to 0.5 parts of a flow agent, which can be 0.2 to 0.3 parts. As one embodiment of this invention, the flow agent can be fumed silica, specifically fumed silica N-20 and / or fumed silica M-5.
[0046] In one embodiment of the present invention, the particle size of the powder coating used for the steel structure of the coastal photovoltaic field can be 120 mesh.
[0047] This invention also provides a method for preparing the powder coating for steel structures in coastal photovoltaic fields as described in the above technical solution, comprising the following steps:
[0048] The powder coating for use on steel structures in coastal photovoltaic fields is obtained by mixing organosiloxane-modified polyester polymer, cyanate compound, low-temperature accelerator, polyacrylic resin, anti-scratch agent, brightener, pigments and fillers, degassing agent, UV absorber and flow agent, followed by melt extrusion and crushing.
[0049] In one embodiment of the present invention, the mixing device can be a mixer. In one embodiment of the present invention, the extrusion device can be a twin-screw extruder; the melt extrusion temperature can be 115–150°C, or 120–140°C. In one embodiment of the present invention, the product after melt extrusion is in sheet form.
[0050] In one embodiment of the present invention, the crushed material can be sieved to collect the undersize material. In another embodiment, the mesh size of the sieve used for sieving can be 120 mesh. In a specific embodiment, the crushing process can be air jet milling.
[0051] This invention also provides the application of the powder coating described above for steel structures in coastal photovoltaic fields as an anti-corrosion coating for coastal steel structure supports. As one embodiment of this invention, the coastal steel structure support can be a marine photovoltaic panel support.
[0052] As one embodiment of the present invention, the method of using the powder coating for steel structures in coastal photovoltaic fields as an anti-corrosion coating for coastal steel structure supports may include the following steps:
[0053] The powder coating used for coastal photovoltaic field steel structures is applied to the surface of the coastal steel structure support and then heat-cured to obtain an anti-corrosion coating.
[0054] In one embodiment of the present invention, the temperature of the heat curing can be 170-190°C or 180-185°C; the time of the heat curing can be 15-25 min or 20-23 min.
[0055] In this invention, during the thermosetting process, the epoxy groups in the cyanate ester compound undergo a high-density polymerization and cross-linking reaction with the end groups in the organosiloxane-modified polyester polymer to form a protective layer structure, reducing the corrosion of coastal steel structure supports by the coastal environment. As one embodiment of this invention, the thickness of the anti-corrosion coating can be 150–300 μm, or even 150–250 μm.
[0056] To further illustrate the present invention, the technical solutions provided by the present invention will be described in detail below with reference to the embodiments, but they should not be construed as limiting the scope of protection of the present invention.
[0057] Example 1
[0058] Polyester resin CRYLCOAT 4540-0, organosiloxane and butyltin triisooctanoate catalyst were mixed in a weight ratio of 40:50:1 and then condensed at 180°C for 5 h in a nitrogen atmosphere to obtain organosiloxane modified polyester polymer.
[0059] By weight, 100 parts of organosiloxane modified polyester polymer, 7.3 parts of triglycidyl isocyanate, 0.2 parts of monobutyltin oxide FASCAT 4101 (low temperature accelerator), 2.8 parts of polyacrylate (HL988 purchased from Huangshan Huahui Technology Co., Ltd.), 2.2 parts of anti-scratch agent NEW-0402, 2.0 parts of 701B brightener, 20 parts of precipitated barium sulfate, 10 parts of mica powder, 10 parts of titanium dioxide, 0.1 parts of carbon black, 0.2 parts of benzoin (degassing agent), 0.8 parts of cyanoacrylate UV absorber (UV-3035), and 0.2 parts of fumed silica N-20 flow agent were mixed in a mixer and then extruded into sheets by melt mixing at 120°C using a twin-screw extruder. The sheets were then ground into powder by air jet milling and finally sieved through a 120-mesh sieve. The undersize material was then collected to obtain a powder coating for steel structures in coastal photovoltaic fields.
[0060] Example 2
[0061] Organosiloxane-modified polyester polymers were prepared according to the method of Example 1;
[0062] By weight, 100 parts of organosiloxane modified polyester polymer, 4 parts of triglycidyl isocyanate, 10 parts of blocked isocyanate, 0.5 parts of monobutyltin oxide FASCAT 4101 (low temperature accelerator), 2 parts of polyacrylate (HL988 purchased from Huangshan Huahui Technology Co., Ltd.), 4 parts of anti-scratch agent HD-901A, 2.0 parts of 701B brightener, 20 parts of precipitated barium sulfate, 14 parts of mica powder, 16 parts of titanium dioxide, 0.1 parts of carbon black, 0.4 parts of benzoin (degassing agent), 1 part of cyanoacrylate UV absorber (UV-3035), and 0.5 parts of fumed silica N-20 flow agent are mixed in a mixer and then extruded into sheets by melt mixing at 120°C using a twin-screw extruder. The sheets are then ground into powder by air jet milling and finally sieved through a 120-mesh sieve. The undersize material is then collected to obtain a powder coating for steel structures in coastal photovoltaic fields.
[0063] Example 3
[0064] Organosiloxane-modified polyester polymers were prepared according to the method of Example 1;
[0065] By weight, 100 parts of organosiloxane modified polyester polymer, 3 parts of triglycidyl isocyanate, 12 parts of blocked isocyanate, 0.3 parts of monobutyltin oxide FASCAT 4101 (low temperature accelerator), 3.8 parts of polyacrylate (HL988 purchased from Huangshan Huahui Technology Co., Ltd.), 3.2 parts of anti-scratch agent HD-901A, 1.0 part of 701B brightener, 20 parts of precipitated barium sulfate, 10 parts of titanium dioxide, 0.1 parts of carbon black, 0.9 parts of benzoin (degassing agent), 0.2 parts of cyanoacrylate UV absorber (UV-3035), and 0.2 parts of fumed silica N-20 flow agent were mixed in a mixer and then extruded into sheets by melt mixing at 120°C using a twin-screw extruder. The sheets were then ground into powder by air jet milling and finally sieved through a 120-mesh sieve. The undersize material was then collected to obtain a powder coating for steel structures in coastal photovoltaic fields.
[0066] Example 4
[0067] Organosiloxane-modified polyester polymers were prepared according to the method of Example 1;
[0068] By weight, 100 parts of organosiloxane-modified polyester polymer, 7.3 parts of triglycidyl isocyanurate, and 1 part of monobutyltin oxide FASCAT are added. 0.4 parts of 4101 (low temperature accelerator), 2.6 parts of polyacrylate (HL988 purchased from Huangshan Huahui Technology Co., Ltd.), 2.6 parts of anti-scratch agent NEW-0402, 1.6 parts of 701B brightener, 20 parts of precipitated barium sulfate, 10 parts of mica powder, 10 parts of talc powder, 10 parts of titanium dioxide, 0.1 parts of carbon black, 0.8 parts of benzoin (degassing agent), 0.6 parts of cyanoacrylate UV absorber (UV-3035), and 0.1 parts of fumed silica M-5 flow agent were mixed in a mixer and then extruded into sheets by melt mixing at 120°C using a twin-screw extruder. The sheets were then ground into powder by air jet milling and finally sieved through a 120-mesh sieve. The undersize material was then collected to obtain a powder coating for steel structures in coastal photovoltaic fields.
[0069] Example 5
[0070] Organosiloxane-modified polyester polymers were prepared according to the method of Example 1;
[0071] By weight, 100 parts of organosiloxane-modified polyester polymer, 7.3 parts of triglycidyl isocyanurate, and 1 part of monobutyltin oxide FASCAT are added. 0.4 parts of 4101 (low-temperature accelerator), 2.6 parts of polyacrylate (HL988 purchased from Huangshan Huahui Technology Co., Ltd.), 3.2 parts of anti-scratch agent NEW-0402, 2.0 parts of 701B brightener, 15 parts of precipitated barium sulfate, 8 parts of mica powder, 15 parts of talc powder, 10 parts of titanium dioxide, 0.1 parts of carbon black, 0.6 parts of benzoin (degassing agent), 0.6 parts of cyanoacrylate UV absorber (UV-3035), and 0.2 parts of fumed silica M-5 flow agent were mixed in a mixer and then extruded into sheets by melt mixing at 120°C using a twin-screw extruder. The sheets were then ground into powder by air jet milling and finally sieved through a 120-mesh sieve. The undersize material was then collected to obtain a powder coating for steel structures in coastal photovoltaic fields.
[0072] Comparative Example 1
[0073] By weight, 0.00 parts of polyester resin CRYLCOAT 4540-0100, 4 parts of triglycidyl isocyanate, 16 parts of blocked isocyanate, 0.1 parts of monobutyltin oxide FASCAT4101 (low temperature accelerator), 2.6 parts of polyacrylate (HL988 purchased from Huangshan Huahui Technology Co., Ltd.), 3.2 parts of anti-scratch agent NEW-0402, 1.8 parts of 701B brightener, 20 parts of precipitated barium sulfate, 10 parts of talc, 6 parts of titanium dioxide, 0.1 parts of carbon black, 0.8 parts of benzoin (degassing agent), and 0.4 parts of fumed silica M-5 flow agent were mixed in a mixer and then extruded into sheets by melt mixing at 120°C using a twin-screw extruder. The sheets were then ground into powder by air jet milling and finally sieved through a 120-mesh sieve to obtain the powder coating.
[0074] The powder coatings prepared in Examples 1-5 and Comparative Example 1 were applied to the surface of a marine photovoltaic panel support and heat-cured at 180°C for 20 min to obtain an anti-corrosion coating with a thickness of 150-250 μm. The performance of the anti-corrosion coatings formed from the powder coatings prepared in Examples 1-5 and Comparative Example 1 was tested according to the following method, and the results are listed in Table 1.
[0075] Table 1 shows the performance of anti-corrosion coatings formed from powder coatings prepared in Examples 1-5 and Comparative Example 1.
[0076]
[0077] As can be seen from the results in Table 1, the coating formed by the powder coating for steel structures in coastal photovoltaic fields provided by the present invention has good impact resistance, corrosion resistance and UV aging resistance.
[0078] Comparing the test results of Examples 1-5 and Comparative Example 1, it can be seen that the content of cyanate compounds in powder coatings affects the impact resistance and corrosion resistance of the coating.
[0079] Although the above embodiments have provided a detailed description of the present invention, they are only some embodiments of the present invention, and not all embodiments. People can obtain other embodiments based on these embodiments without creative effort, and these embodiments all fall within the protection scope of the present invention.
Claims
1. A powder coating for steel structures in coastal photovoltaic fields, characterized in that: The composition comprises the following components in parts by weight: The terminal groups of the organosiloxane-modified polyester polymer include hydroxyl groups or carboxyl groups.
2. The powder coating for steel structures in coastal photovoltaic fields according to claim 1, characterized in that: The preparation method of the organosiloxane-modified polyester polymer comprises the following steps: The polyester resin, the organosiloxane and the catalyst are mixed and subjected to a condensation reaction to obtain the organosiloxane-modified polyester polymer.
3. The powder coating for steel structure in coastal photovoltaic field according to claim 2, characterized in that: The mass ratio of the polyester resin to the organosiloxane is 30-60:40-70; The mass ratio of the polyester resin to the catalyst is 30-60:0.5-5.
4. The powder coating for steel structure in coastal photovoltaic field according to claim 2 or 3, characterized in that: The condensation reaction temperature is 150-200° C. and the reaction time is 4-6 hours.
5. The powder coating for steel structure in coastal photovoltaic field according to claim 1, characterized in that: The particle size of the powder coating used for the steel structure in the coastal photovoltaic field is 120 meshes.
6. The powder coating for steel structure in coastal photovoltaic field according to claim 1, characterized in that: The cyanate compound is triglycidyl isocyanurate and / or blocked isocyanate; The low temperature accelerator is one or more of monobutyltin oxide, butyltin acid and Amanda TH01; The degassing agent is benzoin; The pigments and fillers include one or more of kaolin, precipitated barium sulfate, mica powder, talcum powder, titanium dioxide and carbon black; The flow agent is fumed silica.
7. The method for preparing the powder coating for steel structure in coastal photovoltaic field according to any one of claims 1 to 6, comprising the following steps: The organic siloxane modified polyester polymer, cyanate compound, low temperature accelerator, polyacrylic resin, anti-scratch agent, brightener, pigment filler, degassing agent, UV-resistant absorber and flow agent are mixed, melt-extruded and crushed to obtain the powder coating for the steel structure of the coastal photovoltaic field.
8. The preparation method according to claim 7, characterized in that: The temperature of the melt extrusion is 115-150°C.
9. Use of the powder coating for steel structures in coastal photovoltaic fields as claimed in any one of claims 1 to 6 as an anti-corrosion coating for coastal steel structure supports.
10. The use according to claim 9, characterized in that: The method for using the powder coating for steel structures in coastal photovoltaic fields as an anti-corrosion coating for coastal steel structure supports comprises the following steps: The powder coating for the steel structure in the coastal photovoltaic field is applied to the surface of the coastal steel structure support and thermally cured to obtain an anti-corrosion coating; The temperature of the thermal curing is 170-190° C., and the time is 15-25 minutes.
Citation Information
Patent Citations
Marine-weather-resistant powder coating containing graphene and preparation method thereof
CN106905822A
Filter powder coating and preparation method thereof
CN112778883A
Solid siliconized polyester resins for powder coatings
US20050136267A1
Cited By
Lightweight powder coating based on furfural-fluorocarbon modified polyester resin and preparation method thereof
CN121495445A